Optimal bailout during currency and financial crises: A sequential game analysis - Gabriela Mundaca (University of Oslo, Department of Economics, 2002)
We present a model that illustrates the close relationship between the possibility of a currency crisis and the amount of private-sector debt within a four-stage sequential game framework. In the first stage, the government announces its exchange rate policy, and all agents in the economy receive probabilistic information about a future shock that will occur in the last stage. This shock will affect unemployment and net returns on private sector investment. The private sector in stage 2 forms expectations about the future exchange rate and engages in risky investments. In stage 3, the government faces costs due to expectations of future devaluation and private-sector debt, anticipating the stochastic shock that will occur in stage 4 and may or may not find it optimal to pre-emptively abandon its fixed exchange rate policy. The government can commit already in stage 1 to bailing out part of the private sector's outstanding debt if a bad shock occurs or wait until stage 4 to give an optimal bailout. A commitment to bailing out provides a reconciliation of the multiple equilibria that result from self-fulfilling expectations. Moreover, the government may sometimes avert currency crises by committing to bailing out.
Keywords: E44; F30; F41; 330; currency crisis; private-sector debt; sequential game analysis; financial crises; Währungskrise; Unternehmenssanierung; Auslandsverschuldung; Spieltheorie; Theorie; Extensives Spiel